Microfinance Institutions Performance and Economic Growth In Cambodia: an Advanced Econometric Analysis - Chantha, kong; Seng, Sem; Ratha, Phon; Sovanvatthana, Kol (Economics and Business Journal (ECBIS), 2024)
This study examines the impact of Microfinance Institutions' (MFIs) performance on economic growth in Cambodia, using annual panel data from 62 MFIs for the period 2017–2023. Employing advanced econometric techniques, the findings reveal nuanced relationships between key indicators of MFI performance and GDP growth. Notably, Non-Performing Loans (NPLs) show an unexpected positive relationship with GDP growth, highlighting the Cambodian microfinance sector's resilience in mitigating adverse effects through sustained economic activity. Inflation is also positively associated with GDP growth, suggesting that moderate inflation can drive economic expansion, though careful management is necessary to avoid destabilization. Conversely, the study finds a negative relationship between the number of MFIs and GDP growth, indicating potential inefficiencies from sector oversaturation. Lastly, a positive link between Return on Equity (ROE) and GDP growth underscores the importance of profitability in ensuring financial stability and economic development. The findings emphasize the need for policy measures to manage sector growth, maintain moderate inflation, and enhance MFI profitability for sustainable economic progress in Cambodia.   Keywords: Microfinance Institutions (MFIs); Cambodia; Economic Growth.